PENAMBAHAN KONSENTRASI ASAM LEMAK BEBAS MINYAK JELANTAH TERHADAP KARAKTERISTIK ETANOL SEMI PADAT - Fadel Al Barra; Fajar ' Restuhadi; Usman ' Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research was aimed to obtain a concentration of free fatty acid of waste-cooking oil that obtained the best semi-solid ethanol. This research used the completely random design with 5 treatments with 3 times repetitions for each treatment. Data were analyzed using ANOVA, when F count is greater or equal to F the table then continued by DNMRT at 5% level. The results of this research shows that the addition of various concentrations of free fatty acid significantly affected the real effect (P<0.05) to combustion residue, heat caloric value, heat transfer, and the degree of acidity (pH). The best formulation was the treatment A2 (free fatty acid concentration of 5%) having a viscosity of 16,797 cP, the heat caloric value 23.029 J/g and combustion residue 39,26%. Keywords: Ethanol, free fatty acids, ethanol semi solid.